Tissue and Cell Processing : an Essential Guide - Fehily, Deirdre (Wiley-Blackwell, 2012)
"By presenting the latest technological advances and growing national and international regulation, this new book explores state-of-the-art developments in the challenging field of tissue and cell processing. It provides a guide to easier and safer practice in operational principles of preservation, decontamination, and sterilization. Nearly half of the book is devoted completely to tissue- or cell-specific issues relating to processing. With lists of learning points and case studies which consist of sample processing protocols, descriptions of where processing went wrong, sample risk assessments, or validation studies, the authors help you find specific information fast."--